Kepedulian Mahasiswa Kampus dalam Menjaga Kebersihan Sungai untuk Mendukung Kelestarian - Amir Bandar Abdul Majid; M. Galuh Setiawan; Didit Darmawan; Arif Rachman Putra; Samsul Arifin (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The campus cleanup activity is a form of student community service aimed at raising environmental and ecosystem awareness. Rivers play a vital role as clean water sources and habitats for aquatic life, but are often polluted by waste. This situation demonstrates the need for an educational and collaborative approach to changing student behavior toward rivers. This community service initiative's output targets include increasing public awareness of the importance of river cleanliness and improving the condition of the local river ecosystem. The goal of this activity is to improve river cleanliness, thereby creating a clean river environment that is free from various diseases. The method used is Participatory Action Research (PAR), a method that requires direct involvement with a party in identifying a problem, planning activities, and implementing them. The river cleanup effort demonstrated increased public awareness of river cleanliness, consistent with previous findings that river cleanups can increase environmental awareness. The conclusion indicates that this activity achieved its output targets, with recommendations for continued activities to maintain the quality of the aquatic ecosystem.